2017
DOI: 10.4097/kjae.2017.70.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Value of procalcitonin as a biomarker for postoperative hospital-acquired pneumonia after abdominal surgery

Abstract: BackgroundHospital-acquired pneumonia (HAP) is a common complication after abdominal surgery. The aim of this study was to evaluate the role of procalcitonin (PCT) and C-reactive protein (CRP) as early biomarkers for the diagnosis of postoperative HAP after abdominal surgery.MethodsThis study was conducted on 100 patients undergoing abdominal surgery. White blood cell counts, highest body temperature, and serum levels of CRP and PCT were recorded preoperatively and daily postoperatively until postoperative day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…(Independent samples T-test). Abu Elyazed and El Sayed Zakiin in their study found the diagnostic accuracy of PCT for diagnosing post-operative hospitalacquired pneumonia on day 2 with mean level 1.52 ng/mL [10]. Peritonitis and pneumonitis were the major causes of sepsis in our study population.…”
Section: Dutta Et Almentioning
confidence: 50%
“…(Independent samples T-test). Abu Elyazed and El Sayed Zakiin in their study found the diagnostic accuracy of PCT for diagnosing post-operative hospitalacquired pneumonia on day 2 with mean level 1.52 ng/mL [10]. Peritonitis and pneumonitis were the major causes of sepsis in our study population.…”
Section: Dutta Et Almentioning
confidence: 50%
“…PCT was elevated at 2nd, 3rd and 5th POD in nearly 84 % of patients with pneumonia. 26 C O N T E N T…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 In a retrospective study by Zhang et al, 20 infection markers were evaluated in terms of perioperative pneumonia, urinary infections, and superficial surgical site infections in 500 patients who underwent hip and knee arthroplasty and it has been reported that PCT has a high sensitivity (96%) and specificity (100%) in the diagnosis of bacterial infection. In the study conducted by Abu Elyazed et al, 21 PCT and CRP were compared in the early diagnosis of hospital-acquired pneumonia after abdominal surgery; PCT was determined to have higher sensitivity and specificity on postoperative day 2 compared to CRP levels (84% and 72% vs 70% and 60%, respectively). Nie et al 22 also argued that PCT is superior to CRP in the early diagnosis of postoperative infectious complications in traumatic spinal cord injuries and had a significant role in establishing an effective antibiotic treatment regimen in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%